2006
DOI: 10.1016/j.tcs.2006.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical foundations of dynamic program slicing

Abstract: This paper presents a theory of dynamic slicing, which reveals that the relationship between static and dynamic slicing is more subtle than previously thought. The definitions of dynamic slicing are formulated in terms of the projection theory of slicing. This shows that existing forms of dynamic slicing contain three orthogonal dimensions in their slicing criteria and allows for a lattice-theoretic study of the subsumption relationship between these dimensions and their relationship to static slicing formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
(69 reference statements)
0
30
0
Order By: Relevance
“…Forward Slicing is often not executable because the challenge caused by Forward Slicing is defining the semantics captured by a forward slice [5,9,15].…”
Section: Static Slicingmentioning
confidence: 99%
“…Forward Slicing is often not executable because the challenge caused by Forward Slicing is defining the semantics captured by a forward slice [5,9,15].…”
Section: Static Slicingmentioning
confidence: 99%
“…It was claimed that conditioned slicing subsumes any other form of statement deletion based slicing method [29], i.e., the conditioned slicing criterion can be specified to obtain any form of slice. However, a more recent paper [18] showed that the subsumes relationship does not always exist-conditioned slicing does not subsume Korel and Laski dynamic slicing.…”
Section: Conditioned Slicingmentioning
confidence: 99%
“…We have the requirement that the slice and the original program produce the same value for each variable in the chosen set V at the specified execution position and that the path in p ′ up to q ′ followed by using input x is equivalent to that formed by removing from the path T all elements not in the slice. Interestingly, it has been observed that this additional constraint, that F ront(T ′ , q ′ ) = DEL(F ront(T, q), T (i) ∈ N ′ ∧ 1 ≤ i ≤ q), means that a static slice is not necessarily a valid dynamic slice [37].…”
Section: The Path-faithful Dynamic Slicing Criterionmentioning
confidence: 99%
“…Theorem 11 Let S be a linear schema, let ρl ∈ pre(Π(S)) be executable, let V be a 2 Note that this almost exactly a quote from [15] and is taken from [37] set of variables and let S ′ be a quotient of S containing l.…”
Section: The Path-faithful Dynamic Slicing Criterionmentioning
confidence: 99%